Anesthesia for renal transplantation in patients with dilated cardiomyopathy: a retrospective study of 31 cases - Goyal,Vipin Kumar (2019)
Abstract Background and objectives: Dilated cardiomyopathy is a state of progressive enlargement of cardiac chambers mainly left ventricle which leads to decreased cardiac output and ultimately cardiac failure. Although it has multifactorial etiology, it is quite common in patients with end stage renal disease who require renal transplant surgery for their cure. Both conditions go side by side and anesthetic management of such cases poses real challenge to anesthesiologist. Strict monitoring and control of cardiac physiology is of utmost importance besides meticulous fluid management, thus preserving renal blood flow on one hand and preventing cardiac failure on other hand. This is the basis of achieving good outcome of the renal transplant surgery. Methods: This is a retrospective observational study done by analysing electronic database of 31 patients with dilated cardiomyopathy who underwent renal transplant surgery. Data was studied in terms of demographics, duration of renal disease, comorbidities mainly hypertension, cardiac echo graphic findings including ejection fraction, medications and post-operative outcome. Results: Most common perioperative complication in this patient population was hypotension (51.61%) followed by pulmonary complications postoperative mechanical ventilation (12.9%) and pulmonary edema (6.45%). High incidence of hypotension may be a causative factor to increased rate of delayed graft functioning (12.9%) and acute tubular necrosis (2.23%) in these patients. Conclusion: Strict monitoring and control of hemodynamic parameters as well as meticulous fluid therapy is the cornerstone in improving outcome in patients with dilated cardiomyopathy undergoing renal transplant surgery.